Effect of irrigation, nutrient levels and crop geometry on growth and yield of dill (Anethum sowa L.) - Sharma Y K, Mehta R S, Anwer M M, (Journal of Spices and Aromatic Crops, 2012)
A field experiment was conducted during rabi season at Ajmer (Rajasthan) to study the growth, profitability and productivity of dill (Anethum sowa L.) as influenced by irrigation and nutrient levels with varying crop geometry. Three irrigation levels (12, 15 and 18 days interval) in main plot, three nutrient levels (N and P2O5 each at 60 + 30, 90 + 40 and 120 + 50 kg ha-1, respectively) in sub plot and three crop geometry patterns (40 × 25 cm, 50 × 25 cm and 60 × 25 cm) in sub-sub plot were studied. The highest plant height at all the growth stages was recorded with irrigation at 12 days interval but higher branches plant-1, dry matter plant-1, yield attributes, seed yield, straw and biological yield of 1.2, 2.1 and 3.3 t ha-1 respectively, as well as net return (Rs.15,428 ha-1) and benefit : cost ratio (0.74) was recorded with irrigation at 15 days interval. Higher plant height, dry matter accumulation at all growth stages, yield attributes, seed yield (1.2 t ha-1), straw (2.1 t ha-1) and biological yield (3.3 t ha-1) as well a net return (Rs. 14,464/-) and benefit : cost ratio (0.69) were obtained with application of 90 kg N and 40 kg P2O5 ha-1 being at par with 120 kg N and 50 kg P2O5 ha-1. Crop geometry of 50 × 25 cm resulted in higher seed (1.2 t ha-1), straw (2.1 t ha-1) and biological yield (3.3 t ha-1) over 60 × 25 cm. Thus, application of irrigation at 15 days interval with 90 kg N and 40 kg P2 O5 ha-1 at 50 × 25 cm crop geometry was optimum for realizing higher yield, profitability and productivity of dill.